(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article attempts to formulate a scheme of the structural unity of the physical world of the picture, based on methodological principles. The achievement by scientists of new fundamental results in physical science leads to a change in the scientific picture of the world. In improving the methodology of teaching FKM, its functions are considered: systematizing, explanatory, heuristic and informative.